Political Borders and Bank Lending in Post-Crisis America - Chavaz, Matthieu; Rose, Andrew K (Review of Finance, 2019)
Abstract We study political influences on private banks receiving government funds. Using spatial discontinuities associated with congressional district borders, we show that recipient banks of the 2008 Troubled Asset Relief Program (TARP) program increased mortgage and small business lending by 23–60% more in census tracts located just inside their home-representative’s district than just outside; the effect also shows up in higher loan acceptance rates, and mortgages more likely to be impaired or in default. The effect is stronger when the representative voted for TARP, is politically powerful, connected to the financial industry, and when the bank is important in the district. These findings suggest that obtaining public funds subjects firms to political influences, which affects the quantity and quality of corporate investment because of political considerations.